The Role of Readiness to Change in Fostering to change from Transformational Leadership, Self Efficacy, Behaviour on Performance in Digital Industry - Wijaya, Andreas; Sutojo, Albert; Nicholas, Nicholas (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The role of readiness to change in digital transformation is critical because it influences the success rate of accepting and implementing new technologies within an organization. Readiness to change allows individuals and organizations to adapt to environmental changes, overcome obstacles, and adopt changes more effectively This study distributed an online survey via Google Forms to 237 SME employee. After the survey was completed, data filtering and processing were carried out using SmartPLS The results demonstrate that attitude significantly affects performance. Studies consistently show that individuals with a good attitude can improve their performance. Similarly, the impact of attitude on readiness for change mirrors these findings: individuals with a positive attitude are more motivated and ready to embrace change, which in turn enhances their performance. Evidence shows that employees ready for change experience significant performance growth. In conclusion, readiness for change mediates the relationship between transformational leadership and performance. Employees need guidance and actions from leaders to reach optimal performance. Similarly, readiness for change mediates the relationship between attitude and performance. Furthermore, readiness for change also mediates the effect of self-efficacy on performance, highlighting that self-efficacy drives internal motivation towards goal achievement.